The effect of forest-based health and wellness on the stress-relieve of middle-aged people - Quan, Wei; Yu, Shaona; Huang, Qi; Ying, Miaomiao (Frontiers in Public Health, 2024)
In order to explore the impact of experience in forest-based health and wellness (FHW) on the stress of middle-aged people, 12 participants aged 35–39 were selected to conduct a 3-day/2-night study on FHW experience in Wencheng, Wenzhou. Huawei bracelets were used to monitor participants’ movement, pulse and blood pressure and their mood state was measured before and after the health care experience using the Profile of Mood States (POMS) scale. After the FHW experience, the lowest value of bracelet stress appeared on the second day of the experience for men and women. The total mood disturbance (TMD) decreased by 38.8 points on average, which significantly improved the positive mood and relieved the stress. The decompression effect of the FHW experience showed some variability among individuals. Furthermore, there were gender differences in alleviation of fatigue and puzzlement, which was greater for females than males.